Economical relations between The Extremity Maghreb and Western Sudan during The Eighth Century AH, Fourteenth century AD - Adam, Assadik Ahmad; Daway, Mahamat Saleh (Arab Journal for Sciences and Research Publishing, 2024)
This research explores the economic relations between the Extremity Maghreb (Morocco) and Western Sudan during the 8th century AH (14th century AD). It aims to uncover ambiguities regarding economic and trade relations between the two regions, focusing on the Saharan trade system and the role played by merchants in strengthening trade ties. The study also highlights that the desert was not an obstacle to trade. The researcher employed a historical method to collect and analyze data from various sources. Key findings show that economic relations fluctuated between good and bad, with salt, gold, and slaves being the main traded goods. The study recommends enhancing economic relations, developing trade routes and cities connecting the two regions, and ensuring security and water availability for desert trade.
Keywords: Economic relations; Extremity Maghreb; Western Sudan; Saharan trade; 8th century AH